Peripheral Regions in Duress: Counter-Social Capital Impediments of Local Development in Rural Greek Areas - Elias Kourliouros; George Korres; Emmanuel Marmaras; George Tsobanoglou (European Regional Science Association (ERSA), 2006)
Unlike most enthusiastic narratives of various success stories in recent North European regional economic development led by innovation, localized learning, social capital and institutional embeddedness, this paper deals with a set of major stresses and problems of local economic development in peripheral, less favoured, regions. By drawing upon concrete research experience of regional development projects we try to shed light upon the processes of spatio-economic change and the management of local production in connection with prevailing cultural attitudes/values in less developed Greek rural areas. attidudes/values constituting a kind of localized "counter-social capital" deposit that impedes any likely innovative local development initiatives. The paper argues that the major problems facing these areas are not only or solely associated with the effects of market economy restructuring and the operation of macroeconomic and macropolitical forces at the regional and local level, but, also with inadequate management of human skills, lack of productive mentality and negative cultural values and attitudes. The policy relevance of our analysis calls for the elaboration of alternative development strategies aimed rather at enchancing local social capital potentialities than at improving hard infrastructures and providing financial incentives to local firms.
Keywords: 330